In vivo kinetics of Wolbachia depletion by ABBV-4083 in L. sigmodontis adult worms and microfilariae. - Marc P Hübner; Marianne Koschel; Dominique Struever; Venelin Nikolov; Stefan J Frohberger; Alexandra Ehrens; Martina Fendler; Iliana Johannes; Thomas W von Geldern; Kennan Marsh; Joseph D Turner; Mark J Taylor; et al. (Public Library of Science (PLoS), 2019)
Depletion of Wolbachia endosymbionts of human pathogenic filariae using 4-6 weeks of doxycycline treatment can lead to permanent sterilization and adult filarial death. We investigated the anti-Wolbachia drug candidate ABBV-4083 in the Litomosoides sigmodontis rodent model to determine Wolbachia depletion kinetics with different regimens. Wolbachia reduction occurred in mice as early as 3 days after the initiation of ABBV-4083 treatment and continued throughout a 10-day treatment period. Importantly, Wolbachia levels continued to decline after a 5-day-treatment from 91.5% to 99.9% during a 3-week washout period. In jirds, two weeks of ABBV-4083 treatment (100mg/kg once-per-day) caused a >99.9% Wolbachia depletion in female adult worms, and the kinetics of Wolbachia depletion were recapitulated in peripheral blood microfilariae. Similar to Wolbachia depletion, inhibition of embryogenesis was time-dependent in ABBV-4083-treated jirds, leading to a complete lack of late embryonic stages (stretched microfilariae) and lack of peripheral microfilariae in 5/6 ABBV-4083-treated jirds by 14 weeks after treatment. Twice daily treatment in comparison to once daily treatment with ABBV-4083 did not significantly improve Wolbachia depletion. Moreover, up to 4 nonconsecutive daily treatments within a 14-dose regimen did not significantly erode Wolbachia depletion. Within the limitations of an animal model that does not fully recapitulate human filarial disease, our studies suggest that Wolbachia depletion should be assessed clinically no earlier than 3-4 weeks after the end of treatment, and that Wolbachia depletion in microfilariae may be a viable surrogate marker for the depletion within adult worms. Furthermore, strict daily adherence to the dosing regimen with anti-Wolbachia candidates may not be required, provided that the full regimen is subsequently completed.